Disturbed: Doing deep transformative work – Reflections on social justice work in South African higher education (Journal of Student Affairs in Africa, 2024)
Alternative dispute resolution, anti-discrimination, anti-bullying, diversity and inclusion in higher education has been the focus of my work over the past four years. Spaces in which I have immersed myself include transformation at the University of the Witwatersrand (Wits) with multiple stakeholders, transformation engagement across the South African higher education system with academics, leaders, and managers and the most recent and perhaps most prominent has been myparticipation in the University of Cape Town (UCT) Panel which was appointed by its Council at the end of 2022 to investigate governance failures at the university as well as my facilitation engagements in transformation at Stellenbosch University since 2023. These experiences have at times been disruptive, disturbing and about learning “to be comfortable with discomfort”, an idea I discuss elsewhere in ‘Doing transformation: Building transformative practices from the bottom-up’ (Johnson et al., 2024). Consistent with this work, this piece is a reflection about sense-making after a series of interactions of deeply challenging and disturbing yet rewarding experiences. In some ways it takes this work forward by thinking more deeply about going deeper into inter-personal transformative practice beyond the blunt instrument of employment equity. My autoethnographic reflections in this piece are part of my larger body of work on change theory or what we may encounter as activists, professionals, leaders, and managers in doing change. In this article, I consider what doing deep transformative work may entail, what it reveals, how we may come to understand it and what we may consider as tools and ways to engage with our woundedness as expressed within the self, interpersonal relations and systemic relations or, put differently, our engagement with the expressions of the systemic within the self. This work is a reminder that even the most advanced, highly acclaimed, and esteemed colleagues and scholars do not levitate above society, nor do our institutions, as we all carry our humanness and fallibility. It is also a reminder that all scholars are not necessarily leaders. The task however is to confront ourselves in terms of how we can make better contributions in how we lead change.